Protein Tyrosine Phosphorylation in Human Platelets during Shear Stress-Induced Platelet Aggregation (SIPA) Is Regulated by Glycoprotein (GP) Ib/IX as well as GP IIb/IIIa and Requires Intact Cytoskeleton and Endogenous ADP - Oda, Atsushi; Yokoyama, Kenji; Murata, Mitsuru; Tokuhira, Michihide; Nakamura, Kosei; Handa, Makoto; Watanabe, Kiyoaki; Ikeda, Yasuo (Thrombosis and Haemostasis, 1995)
Shear stress-induced platelet aggregation (SIPA) may be essential in thrombus formation in pathologically stenotic arteries. Intracellular events during SIPA are, however, poorly understood. Washed platelets were exposed to shear stress (108 dyne/cm2) in the presence of von Willebrand factor (vWf, 10 μg/ml) and 1 mM CaCl2 for various time intervals, and then lyzed in SDS. Platelet proteins were separated by 10% SDS-PAGE and tyrosine phosphorylated proteins were detected by immunoblotting with an anti-phosphotyrosine monoclonal antibody. Increased tyrosine phosphorylation of proteins of 130, 100, 85, 74, 70, 64, 58, and 40 kDa was observed within 30 s after the beginning of exposure of platelets to high shear force and the degree of tyrosine phosphorylation continued to increase up to approximately 2 min after the exposure. A monoclonal antibody (MoAb) against vWf-binding domain of glycoprotein (GP) Ibα (GUR83-35), anti-vWf MoAb that inhibits binding of vWf to GPIbα (NMC-4), or a MoAb against GP IIb/IIIa complex (AP-2) inhibited SIPA as well as tyrosine phosphorylation of these proteins. Apyrase (an ADP scavenger, 2 U/ml), EDTA (5 mM), or RGDS peptide (200 μg/ml) also had inhibitory effects on both SIPA and tyrosine phosphorylation. However, Cytochalasin D (2 μM) or staurosporin (1 μM) did not affect SIPA, while they inhibited SIPA-associated tyrosine phosphorylation of those proteins. SIPA-associated tyrosine phosphorylation is a novel post-aggregatory pathway in signal transduction, which is dependent on the binding of vWf to GP Ib/IX and GP IIb/IIIa, endogenous ADP, and intact cytoskeleton.